“Sareupna” Reinterpretasi Tradisi Pamali Sebagai Penciptaan Karya Seni Lukis - Monique, Dilasyaneu; Rohandi, Teten; Kusdiana, Hilman Cahya (ATRAT: Jurnal Seni Rupa, 2025)
Pamali is an oral tradition that acts as a social control that incorporates ethics and values through prohibitions or taboos, especially in children’s daily life, social life, time and place restrictions. The creation of this final project departs from the phenomenon of the fading value of the pamali tradition, especially the prohibition of activities before Maghrib in today’s younger generation. The visuals of this painting use a parody approach by combining elements of horror and facetiouness, as well as combining traditional symbols. Through humorous and witty visual exploration, pamali is no longer presented as something scary, but rather as a reflective cultural dialog and open to reinterpretation of its meaning. The creation method used is the practice-led research method, which is research conducted during the practice of the work, which is divided into three stages: (1) Pre-image stage; (2) Abstract image stage; (3) Abstract image stage. The result of this creation is a total of 3 canvases using acrylic paint, each illustrating the pamali expressions of Maghrib time.